الرياضة المدرسية من بين آليات تعزيز روح المواطنة - بن ققة, سعاد; علي شريف, حورية (Tamayoz, 2019)
تقوم المدرسة بعدة وظائف منها التربوية والاجتماعية والسياسية وغيرها، مستعملة في سبيل تحقيق ذلك عدة وسائط. من بين المواد الدراسية، كمادة التربية البدنية والرياضية، والتي يعتبرها الغالبية مجرد حصة ترفيهية غير واعين بأبعادها البالغة الأهمية، والتي يمتد تأثيرها إلى المجتمع ككل. بناء على ذلك، سيقوم هذا المقال بالكشف عن دور الرياضة المدرسية في تعزيز روح المواطنة، وهذا من خلال الكشف عن دورها في تحقيق الوحدة الوطنية و تعزيز ثقافة السلم. Summary .          The school has several functions, including educational, social, political and other, used to achieve this in several ways. Among the subjects, such as physical education and sports, which are considered by the majority as a recreational share is not aware of the dimensions of the most important, which extends to the community as a whole.      Accordingly, this article will reveal the role of school sports in promoting the spirit of citizenship, by revealing its role in achieving national unity and promoting a culture of peace.